El conocimiento didáctico del contenido y su impacto en los conocimientos prácticos de los profesores de ciencias y en la construcción de conocimientos científicos escolares - Mosquera Suárez, Carlos Javier; Alonso, Maritza Ximena; García-Supelano, Ana María; Marín-Velasco, Astrid Sisleny; Prada-Murcia, Luis Eduardo; Rincón-Nuñez, Juan Pablo; Saldaña-Lozano, Luis Santiago (Revista Científica, 2021)
In this paper show some results achieved in the research project entitled "Practices of chemistry teachers training and their relationship with the development of scholar scientific activities", supported by Centro de Investigaciones Científicas from the Universidad Distrital Francisco José de Caldas. The approach to fundamental theoretical issues is sought to understand, from the field of knowledge in Teaching of Natural Sciences, the model of Didactic Content Knowledge and its relationship, in the field of science teacher education, with the development of practical knowledge in teaching-learning contexts to promote the development of scholar scientific knowledge.